(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the state-level attention being paid to women’s issues by the President of our country. It outlines the role of women in the family, as well as the measures being taken to improve their social protection and working conditions. The article also addresses existing problems related to women in the family and society, and provides scientific conclusions regarding possible solutions.